Pencegahan Penyebaran Covid-19 Melalui Peningkatan Disiplin Protokol Kesehatan di Desa Sungai Kakap, Kabupaten Kubu Raya - Netty Herawaty; Lina Sunyata; Ully Nuzulian; Ratu Zahira Lutfie; Nahot Tua Parlindungan Sihaloho (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Although the number of positive confirmed cases of Covid-19 in Kubu Raya Regency is quite high, people still choose to continue their activities as they should without worrying that the number of positive Covid-19 patients in Indonesia continues to grow. To overcome the problem of the lack of Covid-19 information in the village, this is done by providing direct understanding to the community in the village with a program to increase public understanding about the potential for preventing Covid-19 transmission, namely Community Service which is carried out through several important concrete actions, namely by providing outreach to the community. the community with the interview process about their previous understanding of the Covid-19 pandemic, the way to prevent the spread of COVID-19 is to practice good and correct hand washing. This activity took place in Sungai Kakap Village, Sungai Kakap District, Kubu Raya Regency. This activity aims to increase public awareness and lifestyle during the Covid-19 pandemic. This activity was carried out in four stages during the day, which included socialization, counseling, installation of information banners, and distribution of masks. The result of this Community Service activity is an increase in public awareness about the importance of discipline in implementing health protocols in every activity outside the home. Increased public knowledge is known through increasing the results of the initial test (pre-test) and final results (post-test). This program is expected to be sustainable with many benefits for the community to prevent the transmission of Covid-19.